Study of scattering characteristic of thin ice‐water layers covered dielectric material utilizing hybrid implicit‐explicit finite difference time‐domain method. (13th December 2021) - Yan, Wenbin; Cao, Qunsheng; Wang, Yi
Abstract: In the paper, a hybrid implicit‐explicit finite difference time‐domain (HIE‐FDTD) method is applied, and the related calculation formula of the HIE algorithm is derived in detail. Using the HIE‐FDTD method, the scattering characteristics of dielectric objects covered with very thin ice water layers are studied. The dispersive medium model of the mixture of water and ice is expressed in Debye form and can be calculated by the auxiliary difference equation technique. It is found that the change of the scattering characteristics of the water ice mixing layer mainly depends on the proportion of water in the ice water mixture, and describes the process of ice melting into water, which leads to the corresponding changes of reflectivity, transmittance, and absorptivity. Finally, the simulation results show that the HIE‐FDTD method has higher efficiency than the conventional FDTD without losing accuracy.